88.3k views
5 votes
5) –2x – 9y=-25
-4x – 9y=-23

User Erdomke
by
5.2k points

2 Answers

7 votes

Answer:

(-1,3)

Explanation:

-2x-9y=-25

-4x-9y=-23

solve the equation

-9y=-25+2x

-4x-9y=-23

substitute the value of -9y into an equation

-4x-25+2x=-23

minus -4x to 2x. and. minus -25 to -23

2x=-2

divide both aides by 2

x= -1

substitute the value of x into an equation

-9y=-25+2•(-1)

multiply 2 to -1

-9y=-25+-2

add -25 to -2

-9y=-27

divide both sides by &9

y=3

the answer is (-1,3)

User Troll The Legacy
by
4.4k points
2 votes

Answer:

(-1,3)

Explanation:

–2x – 9y=-25

-4x – 9y=-23

Multiply the second equation by -1

4x + 9y=23

Add this to the first equation

–2x – 9y=-25

4x + 9y= 23

-----------------------

2x = -2

Divide each side by 2

2x/2 = -2/2

x = -1

Now we need to find y

4x+9y = 23

4(-1) +9y = 23

-4 +9y = 23

Add 4 to each sdie

-4+4 +9y = 23+4

9y = 27

Divide each side by 9

9y/9 = 27/9

y =3

User Maxeng
by
5.0k points